Synergism effect between internal and surface cubic-large-pores in the enhancement of separation performance in hierarchically porous membranes. (16th January 2023) - Lin, Taotao; Fan, Donglei; Wang, Jiayao; Shi, Jiahui; Ni, Weibiao; Ding, Mingming; Li, Yongjin; Yang, Yong-Biao; You, Jichun
Abstract: In this work, separation performance of hierarchically porous membranes (HPMs) has been investigated with the combination of experiment and finite element simulation. From the blend of poly (vinylidene fluoride), poly (methyl methacrylate) and sodium chloride (i.e., PVDF/PMMA/NaCl), PVDF HPMs with cubic-large-pores connected through narrow nanopores have been fabricated successfully by etching NaCl and PMMA respectively. In the case of extremely high fill of NaCl, the inorganic fillers distribute all-over the specimen, yielding simultaneously internal and surface cubic-large-pores. Relative to the reference with only nanopores, the attained HPMs exhibit much higher permeability (up to ∼200 times) without any loss of selectivity. Such a significant improvement of separation performance can be attributed to the synergism effect between internal and surface cubic-large-pores. On one hand, the high content of isolated large pores in HPMs corresponds to shorter diffusion length and lower diffusion barrier for fluid; On the other hand, the existence of cubic-large-pores on membrane surface produces not only bigger pores and higher porosity on membrane surface, corresponding to convenient diffusion pathway, but also the enhanced hierarchical roughness including narrow nanopores and cubic-large-pores, providing additional driving force for water/oil separation. Graphical abstract: Image 1 Highlights: Simulation results clarify the synergism effect between internal and surface cubic-large-pores. PVDF HPMs with both internal/surface cubic-large-pores and narrow nanopores have been fabricated successfully. The attained PVDF HPMs exhibit higher flux without any loss of rejection ratio during separation.